Continuous Quasi Gyrolinear Functionals on Möbius Gyrovector Spaces - Keiichi Watanabe (Journal of Function Spaces)
We investigate a class of functionals on Möbius gyrovector spaces, which consists of a counterpart to bounded linear functionals on Hilbert spaces.